Methods design concept an effective approach for profitability. - Shigeyasu Sakamoto
A company achieved 1000% increase in profitability with an improvement of around 500% in productivity. One of the factors that lead to the success is the changes made in their approach of methods improvement. That is designing new working methods on white papers rather than analysis of present methods with industrial engineers. I believe, real new and effective methods can be obtained without new appraoch of designing such as MDC.
Profitability oriented management of productivity is also an important matter. Profitability has been declining year by year as well as growth in sales and market shares of Japanese manufacturers. It is not unusual that productivity activities do not directly contribute to corporate performance because of if the productivity improvement is mainly depend on capital investment or autonomy activities. MDC has achieved high level of productivity improvement such as reductions in actual headcounts according to the n umber of workers rather than reducing required man-hours or shortening cycle times through work simplification, KAIZEN approach.
Keywords: Method design concept (MDC).